Ochradenus lakhpatensis (Resedaceae), a new species from Gujarat, India - Patel, Rohitkumar M.; Prajapati, Sujitkumar R.; Martín-Bravo, Santiago (Phytotaxa, 2024)
A new species of the genus Ochradenus (Resedaceae), O. lakhpatensis, is described and illustrated. It is known from just five populations endemic to a relatively restricted area in Western India (Gujarat state), constituting the easternmost known records of the genus. It is morphologically similar to O. harsusiticus but differs in having pedicellate flowers and fruits, a higher number of stamens, wider fruit, and open fruit apex. A detailed description of the new species including colour photographs and an identification key to distinguish currently accepted Ochradenus species are provided. A preliminary conservation assessment of the species is also conducted under IUCN categories and criteria at the global level, resulting in the proposal of the Endangered category. In addition, we propose the exclusion of O. baccatus from the Indian flora, as it seems to be erroneous record.